1989
DOI: 10.1002/jrs.1250200311
|View full text |Cite
|
Sign up to set email alerts
|

Highly resolved depolarization dispersion and excitation profiles of Raman fundamentals of protoporphyrin IX in a cytochrome c matrix

Abstract: New experimental data for depolarization dispersion (DPD) and excitation profiles (EP) with high spectral resolution (20 cm- ') are provided for Raman fundamentals of protoporphyrin IX in ferrocytochrome c between 17000 and 22500 cm-', covering the resonant region of the Q-bands and the pre-resonant region of the B-bands. Both DPD and EPs of the lines at 1312 and 1585 cm-' (Azs), at 1363 cm-' (Als) and at 1621 cm-' (B,#) exhibit sharp structures. These result from multi-mode contributions of vibrations which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 25 publications
(8 reference statements)
4
50
0
Order By: Relevance
“…The occurrence of the former was earlier derived from the DPD of n 19 , but these studies only focused on pure electronic distortions, while Refs. [30,66] show that vibronic distortions are more relevant for understanding the experimental DPDs. Moreover, the exceptionally strong DPD of n 4 for heme proteins (cf.…”
Section: Raman Dispersion Spectroscopy (Rds) On Heme Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…The occurrence of the former was earlier derived from the DPD of n 19 , but these studies only focused on pure electronic distortions, while Refs. [30,66] show that vibronic distortions are more relevant for understanding the experimental DPDs. Moreover, the exceptionally strong DPD of n 4 for heme proteins (cf.…”
Section: Raman Dispersion Spectroscopy (Rds) On Heme Proteinsmentioning
confidence: 97%
“…Though theoretically sound, this approach yielded only a qualitative description of the data. In response to Zgierski's criticism Bobinger et al [66] reported much more detailed REPs and DPDs of four ferrocytochrome c Raman lines, namely, n 4 (A 1g ), n 19 and n 21 (both A 2g ), and n 10 (B 1g ), which covered the entire resonance region of Q 0 and Q v and additionally the preresonant region of the B-band. While the authors employed the theoretical approach of Schweitzer- Fig.…”
Section: Raman Dispersion Spectroscopy (Rds) On Heme Proteinsmentioning
confidence: 97%
“…18 For the vibrational ground state of the Q state, second-order Rayleigh-Schrödinger perturbation theory yields…”
Section: Vibronic Perturbationsmentioning
confidence: 99%
“…17 Schweitzer-Stenner and co-workers performed several resonance Raman dispersion studies to obtain quantum-mechanical parameters which reflect electronic and vibronic perturbations of the cytochrome macrocycle. 18,19 A new and particularly important aspect was added to the debate on heme c distortions when Shelnutt and co-workers described comparatively large out-of-plane deformations ͑ruffling and waving͒, which were found to be mostly conserved for cytochrome c species for which the amino acid residues between the cysteine linkages to the heme group is homologous. 20,21 More recently, Manas et al attempted to explore the influence of heme-protein interactions on the optical properties of the heme group in ferrocytochrome c. 3 They measured the Q-band spectra of horse heart ͑hhc͒, beef, porcine, tuna ͑thc͒, chicken, and yeast cytochrome c ͑yc͒ at cryogenic temperature which allows a better separation of overlapping bands due to the absence of thermal broadening, and reported splittings of different magnitudes for different cytochromes.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent study of resting HRP C, 5 we modeled the depolarization ratio dispersion of several structuresensitive ip modes of the respective heme group by utilizing coupling values obtained from the earlier analysis of Ni(II) porphin 17 and Ni(II) octaethyltetraphenylporphin, 16 and heme proteins such as ferrocytochrome. 18 In the present study, we focused on Raman scattering by oop modes at Soret excitation, for which the intensity arises mainly from BB intra-state coupling. 13 This comprises Franck-Condon coupling for all modes with an A 1g -type Raman tensor and Jahn-Teller coupling for modes with B 1g and B 2g tensors.…”
Section: Raman Intensitymentioning
confidence: 99%